PENGARUH GCG dan CSR TERHADAP MANAJEMEN LABA SERTA DAMPAKNYA PADA TAX AVOIDANCE - Rahmawati Rahmawati (Owner : Riset dan Jurnal Akuntansi, 2022)
This study discusses analyzing and obtaining empirical evidence regarding Good Corporate Governance, and Corporate Social Responsibility regarding earnings management and its impact on Tax Avoidance. This study uses research samples published on the Indonesia Stock Exchange for the period 2013-2017. Hypothesis testing using the Partial Least Square method using Smart PLS 3.0 software. The results showed that corporate social responsibility has a positive effect on earnings management, corporate governance contributes to tax avoidance, earnings management is able to mediate the significant influence of good corporate governance on tax avoidance with a positive direction, and management earnings mediate social responsibility that is not significant towards tax avoidance in a positive direction.